Epidemiologic characterization of human papillomavirus (HPV) infection in various regions of Yunnan Province of China. Issue 1 (December 2016) - Baloch, Zulqarnain; Li, Yuanyue; Yuan, Tao; Feng, Yue; Liu, Yanqing; Tai, Wenlin; Liu, Li; Wang, Binghui; Zhang, A-mei; Wu, Xiaomei; Xia, Xueshan
Abstract Background This study was designed to determine the Human papillomavirus (HPV) prevalence and its distribution of genotypes in various regions of Yunnan Province, China. Method In this study, participants were recruited during routine gynecologic examination between Oct 2013 and Feb 2015. A total of 17, 898 women were recruited. Polymerase chain reaction was used for detecting the HPV positive samples and HPV geno-array test was used for genotyping. Results The overall HPV infection rate (19.9 %) among the south-western women was significantly higher (P = 0.001) than that among the north-western (18.0 %), south-eastern (13.3 %), north-eastern (11.1 %) and central women (12.9 %). The high-risk (HR) (18.1 %, P = 0.001) and single genotype (16.7 %, P = 0.001) infection rates among the South-western women were also significantly higher than those of among the north-western (13.9 %, 11.3 %), south-eastern (11.6 %, 10.5 %), north-eastern (9.6 %, 9.1 %) and central women (10.5 %, 10.0 %), respectively. While, the infections with multiple HPV (4.2 %) genotypes were significantly more common (P = 0.001) among women in north-western Yunnan than women in the south-western (1.3 %, 3.1 %), south-eastern (1.7 %, 2.7 %), north-eastern (1.5 %, 2.0 %) and central Yunnan (2.4 %, 2.9 %). A total of 30 HPV genotypes were detected; among them 13 were HR-HPV, 3 were PHR-HPV (Potential High risk), 8 were LR-HPV (Low risk) and six were unclassified. The most common HPV genotypes were HPV-52, 16, 58, 53 in control group, HPV-16, 52, 58, 39 and 53 in CINI (Cervical intraepithelial Neoplasia), HPV-52, 16, 58, 33, 53 and 81 in CINII, HPV16, 58, 18, 52, 81 in CINIII and HPV-16 18, 58, 52 in cervical cancer (CC), respectively. Such variation has also been observed about distribution of HPV genotypes distribution among single and multiple infections. Conclusion This study gives an epidemiological estimate of HPV prevalence and different genotype distribution in various region of Yunnan province and further explains its prevalence in different neoplastic lesions. Overall HPV-16, 52, 58, and 18 are the leading HR-HPV genotypes.